(3fXQjI GdZdW hCKQg aj GdYbhO aj Gdabg GdESdGej (B:s (3OQGSI ebGQfI (B/ s - (3CMeO YHO GdQMef YHO GdSejY QeVGfs; (3eMehO HdGd egQGfs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 1996)
(3JTJed GdQSGdI Ydi JegjO Yf GdJWhQ GdJGQjNj ddZdW cYjH ddEQGOI, Ke jHOC GdHGH GdChd Yf eGgjI GdZdW cYjH ef YjhH GdEOGQI, Ke GdHGH GdKGfj Yf CKQ GdZdW hCHQR JWHjbGJg(B.s
(3JTJed Ydi (B15 (3UaMI JQLeI ddHGH GdChd ef GdQSGdI HGddZI GdaQfSjI(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B1996.s
(3HHdjhLQGajG(B: (3UaMGJ (B304-332.s
Keywords: (3GdfXQjI GdYGeI ddZdW cYjH s; (3GdZdW hGdYjHs; (3GdZdW hGdJOdjSs; (3GdZdW hGdZHfs; (3TQhW GdZdW s; (3CKQ GdZdWs; (3GdNjGQ hGdHWdGf GdfSHjs; (3GdfXQjI GdYGeI ddZdW cYjH s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 1996